Pengaruh Kualitas Produk, Citra Merek dan Harga terhadap Keputusan Pembelian Produk Frozen Food Merek Golden Farm di Masyarakat Kota Bekasi - Afifah Khoiriyah; Primaraga Sumantri Indra Wicaksana (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the effect of product quality, brand image, and price on purchasing decisions on Golden Farm brand frozen food products in the people of Bekasi City. This type of research uses quantitative methods with data collection methods using questionnaire data collection techniques, data analysis used in this study are validity and reliability tests, classical assumption tests, multiple regression analysis, partial tests, and R2 tests. The results of this study are product quality has a positive and significant influence on purchasing decisions, brand image has no influence on purchasing decisions, and price has an influence on purchasing decisions.